High-throughput hit-squad tackles trypanosomes. Issue 9 (September 2021) - Cook, Alexander D.; Higgins, Matthew K.
Abstract : African trypanosomes cause diseases of humans and their livestock. To date, a much-desired vaccine has been elusive, due in part to the immune evasion mechanisms of these cunning parasites. However, Autheman et al. have used a bold, high-throughput screen to provide hope that vaccines may be on the way.